Reputation, image and influence of the pharmaceutical industry: rebuilding the trust - Parker, Jane (Henry Stewart Talks, 2009)
Challenging times, Negative perceptions, Profiteering, Intensive sales and marketing activities, Poor research and development strategies, Poor productivity and lack of innovation, Safety concerns, Lack of transparency and credible information, Facing the issues, Perception is reality, Rebuilding trust, Creating a single voice, Restoring the industry's image and enhancing the effectiveness of our industry's voice, Innovation, Research and development, Impact, Industry as resource leader